PENGARUH CAHAYA BIRU DALAM FOTOBIOREAKTOR SILINDER TERHADAP PENYERAPAN NITROGEN DAN FOSFAT PADA LIMBAH CAIR PETERNAKAN SAPI SERTA KANDUNGAN KARBOHIDRAT Chlorella zofingiensis DÓ§nz. - , IHDA ZUYINA RATNA SARI; , Prof.Dr.A.Endang Sutariningsih Soetarto, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Microalgae is known to be able to reduce the content of nitrogen (N) and phosphate (P) in the farm waste. The N and P can be used to enhance the growth and carbohydrate content of microalgae. Blue light is also known to be able to enhance the growth of microalgae. The aims of this study were to determine the growth and carbohydrate content of microalgae Chlorella zofingiensis grown in liquid livestock waste medium under blue light treatment and to determine the ability of the microalgae to reduce nitrogen (N) and phosphate (P) in the waste. The study was conducted for 4 days of observation using microalgae C. zofingiensis that grown in medium Â¼ BBM plus liquid livestock waste. Blue light with intensity of 9000 lux and 3000 lux were used as a treatment and white light with intensity of 3000 lux as control. The parameters were the number of cells per day, dry weight, carbohydrate, N and P content in medium at day 0, 2, and 4. The research showed that high intensity of blue light treatment could increase the number of microalgae cells that grown in liquid livestock waste medium up to Â± 2-fold of control. However, increase of cells was not followed by the dry weight per cell of microalgae C. zofingiensis. Furthermore, low-intensity of blue light was able to increase the carbohydrate content per cell and carbohydrate per dry weight up to 0,0078 Î¼g/cell and 132 mg/g, respectively. Microalgae C. zofingiensis treated with high intensity of blue light treatment could reduce the N dan P in the waste up to 31,8% and 13,79%, respectively.